How to draw awesome characters : in easy steps - Turner, Tracey; Clayman, Peter; Bowden, Andrew (DK Publishing, 2025)
The Avengers assemble in Marvel Awesome Characters, a 144 page book that shows artists of all skill levels how to draw characters from the world's most powerful Super Hero team. Inside you'll find drawing projects for Iron Man, Captain America, Black Widow, Hulk, Thor, Ant-Man, Blank Panther, and Captain Marvel. Featuring an introduction to art tools and materials and a series of drawing exercises to allow artists to learn a few basic drawing techniques and drawing projects for your favorite Marvel characters. The easy-to-follow instructions in this book will guide you through the drawing process, each step builds upon the last until the character is complete. You just need a pencil, a piece of paper and find the character you want to draw. You'll learn fun facts about these well-loved characters as you learn to draw them.